Deshidratación osmótica con dos agentes edulcorantes para la conservación de la uvilla (Physalis peruviana L.) - Taffur Párraga, Martha Nataly (2019)
The objective of this research was to evaluate the effect of two types of sweeteners at different concentrations in the osmodeshydration of the uvilla (Physalis Peruviana L.). A Completely Randomized Design was also applied in a 2x2 bifactorial arrangement, with respect to the physico-chemical properties, four treatments were studied with three replications each. 80 g of uvilla in 100 mL of osmotic solution was used as an experimental unit. The factors under study were: type of sweetener: sucrose and honey and concentration of °Brix degrees in the solution with 55 °Brix and 65 °Brix levels. For which Pearson's correlation and dispersion graphs were applied, with respect to osmotic behavior; for the variables weight loss and °Brix, ratifying that, after 10 hours of immersion in the solutions, the phases begin to stabilize, the variation in the grams of fruit and solids are minimal, being evident that T2 (honey of bee 65 °Brix) which achieved a greater effect in both weight loss (36,52%) and solids gain (13,9). The variables evaluated by statistical analysis were: pH, acidity; for the variable pH and acidity there were significant statistical differences, it was established that the treatments with sucrose helped the fruit to be less acidic. The sensory evaluation was carried out by applying the hedonic scale of 9 points, four attributes were evaluated: appearance, smell, texture and flavor, establishing that the untrained tasters chose T3 as the best treatment.